Description of Medical Students' Understanding of Islamic Values in Forming the Professional Character of Muslim Doctors: Literature Review - Ade Lutfia Widya N; Sri Julyani; Rachmat Faisal Syamsu (Journal La Medihealtico, 2026)
Professionalism is a core competency in medical education and requires not only scientific knowledge and clinical skills but also ethical, moral, and spiritual values. In Islamic medical education, values such as amanah, ṣidq, raḥmah, ‘adl, ihsan, ikhlas, and sabar are considered essential in shaping the professional character of Muslim doctors. This study aimed to describe medical students’ understanding of Islamic values and their role in forming the professional character of Muslim physicians. This study used a narrative literature review design. Literature was searched through PubMed/MEDLINE, Google Scholar, ResearchGate, and manual reference searches. From 160 initially identified articles, 15 articles published between 2021 and 2025 met the inclusion criteria and were analyzed using narrative synthesis. The findings showed that medical students generally demonstrated good cognitive and affective understanding of Islamic values, particularly in relation to integrity, responsibility, and spiritual awareness. However, the behavioral implementation of these values in clinical settings remained limited. Several studies showed a gap between students’ understanding of Islamic values and their professional behavior, including low consistency in applying Islamic etiquette and limited courage to report professional misconduct. The internalization of Islamic values was influenced by curriculum integration, role models, academic culture, clinical experience, spirituality, psychological well-being, and peer pressure. This review concludes that Islamic values are highly relevant to medical professionalism, but their implementation requires structured curriculum integration, continuous character assessment, reflective clinical learning, and strong role models from senior clinicians.